Nano-polycrystalline diamond anvils: key devices for XAS at extreme conditions: their use, scientific impact, present status and future needs. Issue 1 (2nd January 2020) - Rosa, A. D.; Mathon, O.; Torchio, R.; Jacobs, J.; Pasternak, S.; Irifune, T.; Pascarelli, S.
ABSTRACT: Nano-polycrystalline diamonds (NPDs) have become fundamental tools for cutting-edge X-ray absorption spectroscopy (XAS) studies at high P/T conditions that opened up new research directions by overcoming previous limitations. Indeed, NPDs yield a continuous and weak X-ray background signal which enables the collection of high-quality XAS data of materials compressed in diamond anvil cells. This is a critical advantage over the classically used single-crystal diamonds that generate strong parasitic signals (glitches) which render the analysis of XAS data in many cases impossible. In this contribution we give an overview of the impact and the scientific opportunities that NPDs opened up for extreme condition XAS spectroscopy at the European Synchrotron Radiation Facility and discuss future needs.